Modeling and optimization of single-leg multi-fare class overbooking problem: the case of Ethiopian Airlines - Bonsa, Getachew Basa (AUC Knowledge Fountain, 2012)
Revenue Management, also known as yield management, is a technique used by airline industries to maximize revenue by allocating the available seats to the right customers at the right price. Overbooking is an airline revenue management technique that enables airlines to sell more seats than available in order to account for the fact that some of the passengers may not show-up or cancel their flights on the departure day. The objective of this thesis is to develop an overbooking model for a single-leg multi-fare class flight considering a realistic distribution of no-show data collected from the Ethiopian airlines. The overbooking model developed considers the interaction (i.e. the transfer of an extra passenger in a lower fare classes to higher fare class empty seat) between classes that may exist during boarding time. Moreover, this work investigates the economic rationale behind the no overbooking policy used by Ethiopian airlines for some of its flights. The overbooking model developed was solved using both a closed form approach using derivatives and Monte Carlo simulation with a derivative free optimization algorithm. A comparison of the revenue generated from no-overbooking policy, the closed form solution, and the Monte Carlo simulation solution approach shows that the Monte Carlo simulation solution approach performs well. Generally, the numerical results show that the overbooking model is effective in determining the optimal number of overbooking for a number of classes and a variety of compensation cost plans.